IMPROVEMENT OF STEGANOGRAPHIC METHOD BASED ON THE ANALYSIS OF COLOR IMAGING MODELS - Юдін, О. К.; Симониченко, Я. А. (Science-based technologies, 2011)
In the article has carried out a research methods to improve the stability of steganographic container up to at-tacks in the time of its transmission of the channels of communication. The main features fixed container was defined, namely a raster image. The analysis of the most common color models images was carried out. A method of rounding meanings elements image for modification low bit was offered. Put the results of the research to justify for the choice of a color model image with increasing stability of steganographic systems.